A fatal postpartum Clostridium sordellii associated toxic shock syndrome. Issue 3 (March 1997) - Bitti, A; Mastrantonio, P; Spigaglia, P; Urru, G; Spano, A I; Moretti, G; Cherchi, G B
Abstract : Clostridium sordellii is an infrequent human pathogen. It has been demonstrated to be occasionally responsible for myonecrosis or gas gangrene. Interestingly, in the obstetric literature, some cases of postpartum maternal deaths have been associated with C sordellii infection causing a rapidly lethal toxin mediated syndrome. This is the first reported case of postpartum death in a 29 year old woman, in which a toxigenic C sordellii was isolated from the patient's blood antemortem during the fatal toxic shock, strongly indicating its role in this rare syndrome.